Effects of heart failure and diabetes on invasive biomarkers of skeletal muscle wasting. (11th May 2022) - Wood, N; Straw, S; Scalabrin, M; Espino-Gonzalez, E; Smith, J; Wheatcroft, S; Witte, KK; Roberts, L; Bowen, TS
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Muscle wasting is common in patients with diabetes mellitus (DM) and chronic heart failure (HF), which exacerbates cachexia and poor quality of life. However, a gap in clinical translation remains as the mechanisms underlying muscle wasting in DM and HF remain poorly validated, with most evidence assumed from experimental small-animal models. Purpose: Validate if markers of muscle wasting (e.g., autophagy, proteolysis, myogenesis) were correlated to muscle phenotype and clinical indices in humans with DM and HF. Method: Male patients with DM (n=4), HF (n=4; NYHA=2), DMHF (n=7; NYHA=2) were included. DM was classified as a HbA1c level ≥48mmol/mol and HF classified as a left ventricular ejection fraction (LVEF) ≤40%, with patients on optimised medication. Muscle biopsies of pectoralis major were excised during routine pacemaker surgery and frozen at -80°C for both histological and gene expression analysis. Muscle samples were sectioned, stained, and imaged for fibre cross-sectional area and fibre type. RT-PCR gene expression was conducted for markers of muscle regeneration (myod, myogenin), protein degradation (myostatin and autophagy-related LC3B, ATG7, CTSL), and anabolic signalling (IGF-1). Statistical analysis included ANOVAs and correlation analysis to identify relationships between variables. Values of p<0.05 were accepted as significant. Results: Groups (DM, HF, DMHF) were not different (P>0.05) in relation to age (79±9, 72±8, 72±10 years) or BMI (24.5±3.6, 28.5±4.2, 29.5±6.0) respectively. Fibre size or fibre type were not different (P>0.05) between groups. In line with this, gene expression for markers of myogenesis and anabolism as well as myostatin were not different (P>0.05) between groups, but a trend in downregulation of the proteolytic autophagy-related genes (LC3B, ATG7, CTSL) in DMHF vs DM or HF was found on average by 21, 36, and 30% respectively. Autophagy-related genes LC3B, ATG7, CTSL were positively correlated (P<0.05) to type IIa fibre numerical density (R=0.82, 0.86, 0.89) and LVEF (R=0.85, 0.92, 0.83), respectively. Conclusion: Our findings indicate that gene expression of autophagy could represent a robust marker of muscle wasting and cardiac dysfunction in humans with DM and HF. Muscle biopsies from patients with DM and HF identified the proteolytic system of autophagy, important for cellular homeostasis, may be inhibited and this was correlated to fibre phenotype and LVEF. However, the process of muscle wasting in DM and HF within the clinical setting may not necessarily reflect those reported in animal models given various other markers were not changed.